Relationship between Prevalence of Iodine Deficiency and COVID.19 - Mosab Nouraldein Mohammed Hamad (جامعة الشيخ عبدالله البدري, 2020)
Iodine is an essential element which is important for synthesis of thyroid hormones to make their biological tasks, insufficiency of this element lead to serious complications that when combined to global crisis, COVID.19 may lead to death. This review focused on relation between prevalence of goiter in connection with COVID.19 and there is no significant linkage between prevalence of goiter and that global health disorder (COVID.19), further studies required to check the role of iodine supplements in treatment or even protection from the complications of COVID.19